Rehabilitación y adecuación de un banco de pruebas Armfield en el Laboratorio de Hidráulica de la UTPL: selección de instrumentación requerida para el estudio de bombas centrífugas y turbinas Pelton y Turgo - Rojas Rojas, Víctor Alejandro (2015)
As part of the initiative to incorporate renewable energy supply system of the campus of the UTPL, play an important role hydro applications whose design requires the use of a pump test to study, in a controlled environment the operation of various types of turbines, in order to transfer the results to implementing solutions hydro field. In this context, it was decided to rehabilitate and adapt the stand Armfield, existing in the Hydraulics Laboratory of UTPL, for the study of centrifugal pumps and turbines Pelton and Turgo type.